Autodepuração do Rio Saco, Maranhão - Feitosa, Josiana do Nascimento Alves (2024)
Water resources are fundamental assets for various purposes. However, the lack of water management has contributed to the pollution of water bodies, exceeding their self-depuration capacity, which is a natural phenomenon that allows the aquatic environment to re-establish its balance after the alterations induced by affluent discharges. With this in mind, this study analyzed the self-depuration process in the Saco River, a tributary of the Itapecuru River in Maranhão. The specific objectives are: to measure the variables related to the self-depuration process of the Saco River; to calibrate, based on the Streeter-Phelps model, the deoxygenation (Kd) and reaeration (Kr) coefficients for the stretch of river under study and; to evaluate the diffuse contribution of biochemical oxygen demand (BOD). The limnological variables were measured at the Sanitation Laboratory (UFPI, Teresina Campus), with the exception of temperature, which was obtained in situ; the hydrometric measurements were taken using a windlass and the Chiu method. The measurements took place between April and December 2023, covering both the rainy and dry periods. The Saco River basin showed a predominance of dense vegetation (coconut forest) followed by exposed soil. The results of the limnological variables were within the limits established by CONAMA Resolution 357/2005 for Class 2 freshwater. With regard to the hydrometric variables, it was observed that the Saco River has a subcritical regime (Fr = 0.09), with an average annual flow of around 2 m³/s. In addition, Chiu's M parameter was equal to 2.16. The calibrated Kd and Kr coefficients were 0.22 day-1 and 2.32 day-1, respectively. The Nash-Sutcliffe efficiency (NSE) coefficient, relating measured and calculated DO, was 0.40, which is acceptable. The simulation using the Streeter-Phelps model and the calibrated data fitted well and showed a good correlation between the diffuse input of BOD and the previous week's rainfall (R² = 0.93). In order for the Saco River to remain in compliance with the CONAMA Resolution for a Class 2 water body, advanced primary treatment of the sewage from the community located near the upstream section of the analyzed stretch is recommended, so that the maximum discharge BOD is 73 mg/L. It can be concluded that the Saco River is self-depurifying, since, despite the discharge of sewage in the upstream section, the BOD value in the downstream section is on average higher than 5 mg/L, in accordance with the CONAMA Resolution.